Truncated distribution of modulus characteristics in natural wood populations

By sorting and improving the veneer sheet, including loading solution permeation, water blocker permeation and compression treatment, the problem of insufficient mechanical properties of veneer sheets and wood sheets is solved, and the effect of improving mechanical properties is achieved.

CN119855691APending Publication Date: 2025-04-18CREATION WOOD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380060658.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-23
Filing Date
2023-08-23
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

During the wood production process, the generated veneer and wood chips have insufficient mechanical properties and cannot meet the strength and modulus requirements of certain structural wood applications.

Method used

The hardness of the veneer sheet in the initial population is measured by non-destructively and classified into groups with a flexural modulus value higher or lower than the target threshold. The veneer with insufficient flexural modulus value is then subjected to loading solution permeation, water barrier permeation, partial drying and compression treatment until its density reaches the target range, thereby increasing its flexural modulus value.

Benefits of technology

The mechanical properties of veneer and wood chips are effectively improved, so that all veneer sheets have acceptable bending modulus values, meeting or exceeding the target performance value, and reducing the existence of low-value outliers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855691A_ABST
    Figure CN119855691A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a method of separating wood veneer materials by means of characteristic measurements, and subsequently improving the characteristics of veneer materials having characteristic values below a target threshold until those materials meet or exceed the threshold. In some aspects of the present disclosure, a veneer material is prepared, measured in a non-destructive manner, and separated into a set of qualified and unqualified materials. A set of unqualified materials may then be processed to improve the density and flexural modulus of the materials therein. Also disclosed herein are articles and materials incorporating treated veneer materials according to the disclosed methods.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 400,332, filed on August 23, 2022, the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present disclosure relates to a method for improving the mechanical property profile of wood veneer materials and veneer-based strand materials, and also discloses products obtained therefrom. Background Art

[0004] Wood products can be classified as structural or non-structural. Structural wood products include softwood glulam, softwood laminated lumber, softwood plywood, laminated veneer lumber (LVL), I-beams, parallel strand lumber (PSL), laminated strand lumber (LSL), European pine board (oriented strand board, OSB) and softwood plywood. Non-structural wood products include particleboard, fiberboard, hardboard and hardwood plywood. Structural wood products are distinguished based on their ability to support sustained loads in buildings and, when used in residential and commercial buildings, mainly involve vertical members, horizontal members, diagonal members and floor, wall sheathing and roof sheathing.

[0005] The strength and modulus properties of wood-based composites are highly dependent on the strength and modulus of the wood elements that make up the composite. The wood elements used to produce structural composites include veneers and wood chips. However, in most cases, a significant percentage of the veneers and wood chips generated on the production site have insufficient mechanical properties for certain structural wood applications. Therefore, there is a need for methods to improve the natural properties of this portion of unsuitable materials and articles using materials having such improved properties.

[0006] Therefore, there is a need for methods of improving the natural properties of these unsuitable materials and for articles using materials having such improved properties. Summary of the invention

[0007] Disclosed herein is a method for converting a population of veneer sheets initially consisting of a mixture of veneer sheets having unacceptable flexural modulus values ​​and acceptable flexural modulus values ​​into an improved population of veneer sheets, wherein all or a majority of the sheets have an acceptable flexural modulus. The method comprises a first step of non-destructively measuring the hardness of the veneer sheets within the initial population. In a second step, the initial population of veneer sheets is classified into a first group having flexural modulus values ​​exceeding a target threshold and a second group having flexural modulus values ​​less than the target threshold. In a third step, the second group of wooden elements undergoes a process of increasing the flexural modulus values ​​so as to exceed the target flexural modulus threshold.

[0008] Certain examples relate to a method that includes subjecting a group of wood veneer sections to a non-destructive, along-the-grain (parallel to the grain) flexural modulus measurement. The method also includes classifying the veneer sections into a first group and a second group, the first group including veneer sections having modulus values ​​above a predetermined threshold, and the second group including veneer sections having modulus values ​​below the threshold. The method also includes subjecting the second group of veneer sections to a process that increases the along-the-grain flexural modulus values ​​to greater than the predetermined threshold.

[0009] Some examples also include a lignin degradation step and a compression step.

[0010] Certain examples also include infiltrating the veneer with a loading solution to produce a treated veneer.

[0011] Some examples also include penetrating the treated veneer with a water barrier.

[0012] Certain examples further include compressing the treated veneer along the thickness axis until a density of the treated veneer is within a first density range.

[0013] Certain examples also include reducing the moisture content of the treated veneer to a range of approximately 1-10%.

[0014] Certain examples further include compressing the treated veneer along the thickness axis until a density of the treated veneer is within a second density range.

[0015] Certain examples relate to a method for improving the mechanical properties of a wood veneer. The method includes infiltrating a wood veneer with a loading solution to produce a treated veneer and partially drying the treated veneer for a first time. The method also includes infiltrating the treated veneer with a water-blocking agent and partially drying the treated veneer for a second time. The method also includes maintaining the treated veneer at a temperature of 20-50°C and a pressure of 100-1,200 psi until the density of the treated veneer is 900-1,100 kg / m 3 , without completely curing the water-blocking agent, and drying the treated veneer until the moisture content is 1% to 10%.

[0016] The foregoing and other objects, features and advantages of the present disclosure will become more apparent from the following detailed description made with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a schematic diagram illustrating a process for improving material properties of substandard veneer and filament materials according to one example. DETAILED DESCRIPTION

[0018] Definition of terms

[0019] The following explanations of terms and abbreviations are provided to better describe the present disclosure and guide those skilled in the art to implement the present disclosure. As used herein, "including" means "comprising", and the singular form "a" or "an" or "the" includes plural references unless the context clearly indicates otherwise. The term "or" refers to a single element of the alternative element or a combination of two or more elements, unless the context clearly indicates otherwise.

[0020] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present disclosure belongs. Although methods and materials similar or equivalent to the methods and materials described herein can be used to implement or test the present disclosure, applicable methods and materials are described below. Materials, methods and examples are illustrative only and are not intended to be limiting. Other features of the present disclosure are readily apparent from the following detailed description and claims.

[0021] Unless otherwise stated, all numerals representing the amount, percentage, temperature, time, etc. of components used in this patent specification or claims should be understood to be slightly modified by the term "about". Therefore, unless otherwise stated (implicitly or explicitly), the numerical parameters described are all approximate values, which may depend on the desired properties sought and / or the detection limits under standard test conditions / methods, as known to those skilled in the art. When the embodiments are directly and clearly distinguished from the prior art discussed, the embodiment numerals are not approximate values ​​unless the word "about" is described. In addition, not all alternatives described herein are equivalents.

[0022] Unless otherwise stated, features described herein with respect to any one example may be combined with other features described in any one or more examples.

[0023] To facilitate review of various aspects of the present disclosure, the following explanations of specific terms are provided:

[0024] Cured: For the purposes of this disclosure, the term "cured" when used in conjunction with monomers means that the monomers have undergone multiple condensation or addition reactions and the resulting reaction products are solid molecules that are insoluble in water.

[0025] Laminated veneer lumber: For the purposes of this disclosure, the term laminated veneer lumber (or LVL) refers to a structural wood-based composite material consisting of multiple layers of veneer, wherein the veneer layers are bonded together using a structural adhesive and the grain angles associated with each veneer layer are oriented in the same direction within the composite.

[0026] Laminated Laminated Timber: For purposes of this disclosure, the term laminated laminated timber (or LSL) refers to a structural wood-based composite material comprised of a plurality of long wood sheets having a length of approximately 6-15 inches and bonded together using a structural adhesive, with the grain angle associated with each sheet being oriented generally along the length of the sheet, and with all sheets being oriented in generally the same direction within the composite.

[0027] Parallel Strand Glulam: For purposes of this disclosure, the term parallel strand gluelam (or PSL) refers to a structural wood-based composite material comprised of a plurality of long wood strands having a length of approximately 30-100 inches and bonded together using a structural adhesive, wherein the grain angle associated with each strand is oriented generally along the length of the strand, and all strands are oriented in generally the same direction within the composite.

[0028] Grain Flexural Modulus: For purposes of this disclosure, the term "grain flexural modulus" refers to a calculated modulus value, wherein the input values ​​for the calculation are determined by a flexure test method involving a rectangular wood-based composite material having a primary grain direction associated with a length axis; wherein the composite material has a width value (w) and a thickness value (t); wherein the composite material is placed on top of two support rods separated by a given distance, and the distance has a specific span value (span); wherein a downward force (F) is applied to the composite material at the center point of the span and parallel to the thickness of the composite material, and the applied force produces a downward deflection distance (d) at the center point of the composite material, and the slope of the F / d relationship is determined; wherein the grain flexural modulus is calculated as (slope x span) 3 ) divided by (4 x width x thickness 3 )

[0029] Oriented Strand Board: For purposes of this disclosure, the term oriented strand board (or OSB) refers to a structural wood-based composite material composed of a plurality of short wood chips, wherein the chips have a length of about 1-6 inches, a width of about 0.5-2.0 inches, and a thickness of about 0.015-0.050 inches, and are bonded together using a structural adhesive, wherein the composite material has a top major surface and a bottom major surface and three or more layers between the top major surface and the bottom major surface, wherein the grain angle associated with each of the chips is oriented generally along the length direction of the chips, and the lengths of the chips in the outermost layers (top and bottom) are primarily oriented along the machine direction, while the lengths of the chips in one or more intermediate layers (between the top and bottom layers) are primarily oriented along the cross direction or have a random orientation, wherein the machine direction of the composite material is offset 90 degrees relative to the cross direction of the composite material.

[0030] Introduction to the disclosed technology

[0031] Structural wood composites can be made from natural wood products such as veneers and wood sheets. The properties of these structural composites depend largely on the properties of the materials that make up the composite. Key engineering properties of structural wood products include flexural strength and flexural modulus. There are a number of standardized test methods to evaluate flexural strength and flexural modulus in structural wood products. Flexural strength values ​​are often expressed as modulus of rupture values, which reflect the cross-sectional shape and size of the wood element and the effects of inherent strength and adhesives on the force required to break the member in a flexural mode.

[0032] Veneers can be made by debarking logs and then immersing them in hot water to ensure that the wood tissue is wet and soft. The wet logs are then cut into shorter segments (usually about 100 inches long), which are called bolts. The bolts are then peeled on a lathe to produce long veneer strips with a thickness of typically from about 0.100″ to 0.250″. The veneer strips are then split into multiple sections (usually about 100 inches parallel to the wood grain direction by about 50 inches perpendicular to the grain direction). The wet veneer sections are then dried and graded based on vision. In some cases, veneers can also be characterized for modulus using a variety of non-destructive evaluation methods (such as x-rays and ultrasound). Once made, the veneers can be used to produce plywood, LVL, PSL or other veneer-based composite products.

[0033] Wood chips can be manufactured in this process, which also begins with debarking logs and then immersing them in hot water to ensure that the wood tissue is wet and soft. The wet logs are cut into wood segments, which are then processed in a chipper. In this stage, the wood segments are laterally pressed into a rotating blade group that cuts the wood segments into thousands of wood chips. Ideally, each wood chip has a length of about 2-6 inches, a width of about 0.5-2.0 inches, and a thickness of about 0.015-0.50 inches. The grain direction of the wood in each wood chip is roughly parallel to the length axis of the wood chip. The wood chip mixture can be dried and then screened (screening) to remove small particles (dust and fine lines). This type of wood chip can be used to produce OSB. Alternatively, wood chips with a length of about 6-15 inches can be used to produce LSL. In some examples, wood chips with a length of about 8 feet can be cut from veneer and then used to make PSL.

[0034] The strength and modulus of these known wooden elements are affected by the part of log that is used to obtain wooden elements. Specifically, log comes from tree trunk. The strongest and hardest wood in the trunk is usually located at the base of the trunk and in the outer layer of the trunk. The wooden element is separated from the center of the trunk and / or the part towards the top of the trunk to produce a wooden element with less strength and less hardness. Strength and hardness may also be affected by the age of the tree when obtained. Trees with larger age tend to produce more solid and harder wooden elements. Interestingly, the strength and hardness of wood also can be affected by the growth rate of trees. Slower growing trees tend to produce more solid and harder wooden elements. Of course, wood species and subspecies types also can affect the strength and hardness of wood. Along with artificially planted trees and young forests becoming more and more common, the strength and hardness of North American wood have all declined usually.

[0035] Based on the above information, it is clear that the wooden elements produced at a given production facility will have a distribution of strength and hardness properties. Traditionally, forest product companies tend to obtain logs from forest land located within about 200-400 miles of the production facility that converts the logs into products. Therefore, production facilities usually process a limited number of logs per year (without incurring significant transportation costs). In addition, the available logs produce wooden elements (veneers and / or wood chips) with a distribution of strength and hardness values.

[0036] For some wood-based composite production facilities, the distribution of wood-based elements' properties can lead to a situation where not all wood-based elements can be used in the manufacturing process. This is particularly true for veneer-based composites (including LVL), which are often used in applications with relatively high flexural strength and stiffness requirements.

[0037] LVL is usually manufactured by applying liquid phenolic binding resin to one or two main surfaces of a veneer sheet using roller coating, spraying, flow coating or other application methods. The veneer sheets treated with adhesive are then combined in a staggered manner into a substantially continuous mat in the machine direction. The grain direction of the veneer is also arranged along the machine direction of the slab. Depending on the thickness of the veneer and the target thickness of the final LVL product, the slab can include about 6-16 layers of veneer sheets in any particular position. The slab is then subjected to hot pressing. The top and bottom press plates in the press may have a temperature of about 330-400°F. The pressure applied to the slab may be in the range of about 100-200 psi. Depending on the target thickness of the final LVL product, the press plate temperature and other parameters, the pressing time may be in the range of about 200-700 seconds. LVL leaves the press as a continuous ribbon that is trimmed on the edges, cut into a certain length, and torn longitudinally according to its intended application. A large amount of LVL is used commercially as flange material for I-beams.

[0038] Wood I-beams are commonly used as horizontal members in subfloors in residential and commercial buildings. I-beams are a competing alternative to solid sawn glulam beams. I-beams are typically attached to frame panels along the perimeter of a building and span between foundation elements on the ground floor. Alternatively, I-beams can span between walls at high floor heights. I-beams can be spaced approximately 16-24 inches apart and serve as substrates and support members for structural subfloor panels. Therefore, I-beams must be very stiff. In fact, I-beams are designed to be exceptionally stiff and lightweight.

[0039] I-beams are made by attaching flange elements to the top and bottom edges of web elements. The web elements are typically OSB with a thickness of 0.375 inches or 0.438 inches or even 0.500 inches. The height of the web can be in the range of about 6-14 inches. The length of the web can be about 8-60 feet. The flange elements can have a width ranging between about 1.375-2.25 inches. The height of the flange elements can be in the range of about 0.75-2.00 inches. The flange elements are typically connected to the top and bottom edges of the web using shaped joints and structural adhesives (resorcinol-based or isocyanate). LVL is the preferred flange material in I-beams.

[0040] The stiffness of the LVL has a major impact on the stiffness of the I-beam. A stiffer I-beam results in less floor movement and vibration (clicking) when occupants walk on the floor in a residential or commercial building. A stiffer I-beam may allow builders to space the beams further apart in a floor system while maintaining the desired structural integrity of the floor, which reduces the cost of the building. A stiffer LVL may also allow the height of the I-beam to be shorter, which helps reduce dead space between floors in a building and reduces the overall cost of the building. Therefore, there is considerable commercial motivation to use a single sheet with the greatest stiffness in the production of LVL and I-beams.

[0041] For a given value of veneer thickness, the stiffness of the veneer is directly proportional to the modulus of the veneer. Therefore, the modulus value is a key indicator of the suitability of a given veneer sheet for LVL applications.

[0042] Unfortunately, in most cases, the veneers generated at the production site include a significant percentage of veneers that have insufficient stiffness (or modulus) for use in LVL and I-beam applications. As an example, a veneer generated at a particular production site may have a stiffness ranging from about 1.5 x 10 6 -2.3x 10 6 psi flexural modulus values. The modulus distribution may be approximately normal with a standard deviation of about 2.0 x 10 5 psi. In addition, the factory may be manufacturing a material that requires a modulus of 2.0 x 106 By intentionally manufacturing LVL with the stiffest veneer in the outermost layers and using less stiff veneer in the middle layers, a factory may be able to take advantage of the fact that the modulus of the veneer is between about 1.8 x 10 6 -2.3x 10 6 psi. Therefore, the modulus is 1.5x 10 5 -1.8x 10 6 psi veneer will be unsuitable for LVL production. In this example, the unusable veneers will constitute about 30.9% of all veneers produced at the factory. In the case where veneer production is expensive and the market price of LVL is high, there are a lot of financial opportunities associated with upgrading the least stiff veneer so that the modulus of the veneer is increased to greater than about 2.0x10 6 The value of is associated.

[0043] Aspects of the Disclosed Technology

[0044] Disclosed herein are methods for identifying properties of veneer and wood chip materials and for improving properties of low-grade veneer and wood chip materials. Also disclosed herein are exemplary composite materials utilizing the improved veneer and wood chip materials.

[0045] There are a number of methods for quickly characterizing the flexural modulus of veneer sheets. Figure 1 In the exemplary method 10 shown, the veneer is separated from the log or wood section by peeling. Then, for example, the peeled veneer is split into the sections shown in the figure using a blade.

[0046] The flexural modulus of the veneer section produced at the manufacturing site along the grain direction can be measured non-destructively. The flexural modulus value test method of the veneer section in the grain direction of exemplary non-destructive is processed by the machine of the veneer supported by rollers at two positions, so that a given veneer sheet spans two rollers and the span has a specific length. Then the third roller can be used to apply a downward vertical load to the veneer at a position equidistant from two support rollers. The force applied from the third roller causes the deflection of a moderate level in the veneer. In a continuous process, multiple groups of load and deflection data can be collected for each veneer sheet. The average force of the load, the average deflection, the span and the average thickness and width of the veneer can all be used to calculate the representative modulus value of the veneer sheet. In practice, the flexural modulus of a single veneer sheet can be characterized in 2-3 seconds using this method. In some examples, the veneer sheet can be processed by a machine measuring the speed of sound propagation through the veneer. The speed of sound can be related to the flexural modulus in a manner that yields reasonable predictions, especially if the ultrasound information is combined with the density of the veneer, which can be determined in an automated manner using an x-ray scanner.

[0047] Continue to refer Figure 1 , once the bending modulus value of the veneer sheet is determined, the veneer sheet can be immediately classified based on whether the measured or estimated bending modulus value exceeds a predetermined threshold. In this way, all veneer sheets produced on site can be classified into an initial "qualified" group or a "failed" group. In some examples, the veneer sheet can be marked with a red or blue stripe or some other visual marking system based on whether the measured bending modulus exceeds a predetermined threshold. The marked sheet can then be classified into a qualified group and a failed group at a later stage of the process. In some examples, only a portion of the veneer sheet generated at the production site can undergo the bending modulus measurement and classification process. In some examples, a veneer with insufficient bending modulus can be transported to a conversion facility from multiple veneer manufacturing plants.

[0048] Thereafter, a veneer that has been designated as having insufficient flexural modulus may be improved in a process that produces a with-grain flexural modulus value that exceeds a predetermined threshold.The disclosed improvement process may be performed in multiple steps.

[0049] In a first step, multiple sections of the veneer are improved by infiltrating the veneer with a loading solution. In some examples, the lignin in the veneer is partially degraded by the loading solution. This lignin degradation step facilitates subsequent compression of the veneer without damaging cells or breaking the lignin. In some examples, a portion of the lignin can also be removed from the veneer in the first step. In other examples, a substantial amount of lignin is not removed from the veneer in the first step. In some examples, the loading solution comprises water, and after treatment with the loading solution, the veneer is heated to a temperature greater than about 50°C.

[0050] In a second step, the treated veneer is at least partially dried.

[0051] In the third step, the treated veneer is infiltrated with a water-blocking agent. The dry mass of the water-blocking agent infiltrated is about 1-50% of the dry mass of the veneer. Preferably, the cells over the entire cross section of the veneer absorb a certain amount of the water-blocking agent. Most preferably, the cells over the entire cross section of the veneer absorb a similar degree of the water-blocking agent, and the absorption occurs mainly in the amorphous cellulose region and the hemicellulose region of the wood cell wall. The dry mass of the water-blocking agent infiltrated may be about 1-20% of the dry mass of the wood.

[0052] In the fourth step, the treated veneer is partially dried a second time. In some examples, the treated veneer is dried gently in a manner that does not cure the water blocking agent.

[0053] In the fifth step, the treated veneer is maintained at a first temperature range of about 20-50°C and subjected to a continuous pressure of about 100-1,200 psi along an axis parallel to the thickness direction of the veneer until the density of the veneer has increased to a first target density range. In some examples, the first target density range may be a density of about 900-1,100 kg / m 3 , without completely curing the water blocker. The moisture content of the compressed veneer may range from about 5-50%.

[0054] In a sixth step, the treated veneer is dried to reduce the moisture content to a second moisture content range of about 1-10%. In some examples, the treated veneer is dried without completely curing the water blocker.

[0055] In the seventh step, the treated wood is maintained at a second temperature range of about 20-150°C and subjected to continuous pressure along an axis parallel to the thickness direction of the veneer until the density of the treated veneer increases to a second target density range. In some examples, the second target density range may be a density of about 950-1,400 kg / m 3 In some examples, once the second density range is reached, the water blocker within the wood is fully cured. The wood that has undergone all seven steps is dimensionally stable and may have a flexural modulus in the longitudinal axis in the range of about 6,000,000-8,000,000 psi (about 41-55 GPa).

[0056] In some examples, the water repellent in the cell wall of the treated wood can be cured after the fifth process step, so that the sixth and seventh steps are omitted. This method can produce dimensionally stable wood products with a density value of about 900-1,250 kg / m 3 And the modulus is about 25-40 GPa. In this example, the temperature of the wood in the fifth step may be in the range of about 20-150°C.

[0057] In some examples, the process omits the third step, that is, the treatment with the water-blocking agent can be omitted. In such examples, the partially dried veneer is secondary dried without the treatment with the water-blocking agent.

[0058] Wood suitable for use as raw materials for the present disclosure includes pine, poplar, fir, poplar, oak, maple, cherry, apple, fir, basswood, Japanese cedar, eucalyptus, etc. In some examples, grass (e.g., bamboo) can be used instead of wood. In some examples, materials from different types of wood can be processed together.

[0059] The veneer lumber sections may have an initial thickness of less than about 0.25". Lumber sections having a thickness of about 0.25" to 0.06" are preferred because they are able to absorb an aqueous loading solution, such as sodium hydroxide or other aqueous solution (including an aqueous solution of a water blocker), uniformly across the entire cross-section of the lumber during the first and third steps of the process.

[0060] The loading solution may include chemicals known to degrade lignin or otherwise modify lignin so that the resulting treated wood may then be compressed to obtain a density greater than about 950 kg / m 3 The loading solution may also promote rapid compression of the wood. The loading solution may include aqueous sodium hydroxide solutions. These solutions may be aqueous sodium hydroxide solutions with a concentration between about 0.1-15.0%. The loading solution may also include sodium sulfite and an oxidant (e.g., ozone, oxygen, hydrogen peroxide, and organic peroxides) or a combination thereof. The loading solution may also include an amine. Preferred amines may include non-volatile low molecular weight amines (e.g., ethanolamine, diethanolamine, triethanolamine, and hydroxylamine). The loading solution may be water-based.

[0061] The veneer can be immersed in the loading solution. In some examples, the veneer through the immersion can experience one or more vacuum cycles to help the loading solution be absorbed into the veneer. Specifically, the veneer section can be placed in a rigid chamber together with the loading solution so that the veneer section is immersed in the loading solution. The valve in the chamber can then be opened, and a portion of the air in the headspace of the chamber can be removed from the chamber by using vacuum. Under vacuum conditions, the air in the veneer section is replaced by an aqueous loading solution at a faster rate than the rate that would otherwise be achieved without vacuum. Additionally or alternatively, the veneer through the immersion can be subjected to positive pressure (e.g., a pressure of 5-15 bars). Specifically, the veneer section can be placed in a rigid chamber together with the loading solution so that the veneer section is immersed in the loading solution. The valve in the chamber can then be opened, and additional air can be discharged into the headspace of the chamber. Under positive pressure conditions, the aqueous loading solution is absorbed into the veneer section at a faster rate than the rate that would otherwise be achieved without positive pressure.

[0062] In the process of immersing the veneer in the aqueous loading solution, the moisture content of the veneer can be increased from a first moisture content of about 1-20% to a second moisture content (dry basis moisture content) of about 20-100%. The process can be carried out at a temperature of 20-200°C. The duration of the loading process can be in the range of about 30 minutes to more than 12 hours, including 60 minutes, 90 minutes, 120 minutes, 240 minutes, 360 minutes, 480 minutes, 600 minutes, 720 minutes or a duration of more than 720 minutes. In some examples, these durations can be considered as the shortest exposure time (i.e., longer time can be used selectively). The required time depends on the size of the veneer, the wood species, the composition of the loading solution, the temperature of the loading solution, and the use of vacuum and / or pressure. Generally, one or more active agents in the loading solution should be distributed over the entire cross section of the veneer when this step is completed. In some examples, one or more active agents in the loading solution can be distributed over the entire cross section of the veneer in a relatively uniform manner. In some cases, the distribution of the loading solution in the veneer may not be uniform, but the distribution will be sufficient to achieve the desired effect of improved veneer compression in subsequent steps of the process.

[0063] After absorbing the loading solution, the treated veneer can be subjected to heat and pressure in a container (e.g., a pressure vessel). The temperature can be in the range of about 20-200°C. The pressure can be in the range of about 1-8 bar. When the temperature is high enough to produce a considerable water vapor pressure, a higher pressure is required. For example, the loaded veneer can be subjected to a pressure of about 5-6 bar and a temperature of about 150-200°C for about 1-5 hours. Under these conditions, a reaction may occur between one or more active agents in the loading solution and lignin, so that lignin is partially (especially at high temperatures) degraded or otherwise improved in a manner that promotes wood softening. Partial degradation generally involves reducing the molecular weight of lignin, but not to the extent that lignin becomes water-soluble. In some examples, the temperature of the loaded wood can be adjusted to increase or reduce the amount of degraded lignin in the wood, so as to reach a degree that is conducive to subsequent compression steps. The temperature value associated with the process can be in the range of about 60-200°C. In some examples, one or more active agents in the loading solution degrade or otherwise improve the lignin and hemicellulose in the wood. By evaluating the compression ratio in the subsequent compression step, the time required for this step can be optimized empirically. Once the target degree of modification has been achieved, the veneer in the pressure vessel will be cooled to a temperature of about 20°C and the pressure on the veneer can be reduced to about 1 bar. In some examples, the treated and conditioned veneer is immersed in or obtained in water to remove lignin that has been inadvertently degraded to the point where it becomes water soluble.

[0064] The moisture content of the treated veneer with modified lignin can then be reduced. In some examples, the moisture content of the treated veneer can be reduced to about 10-20% under mild drying conditions before subsequent processing steps. Drying can be accomplished by using a kiln or an oven. Alternatively, drying can be achieved by placing the treated veneer into a chamber and then reducing the pressure in the chamber. In some examples, the treated veneer can be constrained in a manner that prevents dimensional deformation from occurring during the drying process. Partial drying of the treated veneer can help absorb water-blocking agents in subsequent processing steps.

[0065] Water blockers can include hydrophilic reactive monomers, hydrophobic reactive monomers, waxes, paper sizing agents, drying oils, topical sealants, coatings, and other materials or combinations thereof that inhibit water absorption in treated wood. One particularly advantageous class of water blockers is hydrophilic reactive monomers. One exemplary class of hydrophilic reactive monomers is hydroxymethylated phenols. Another exemplary class of hydrophilic reactive monomers is hydroxymethylated substituted phenols, such as hydroxymethylated cresols. One exemplary class of hydrophobic reactive monomers is isocyanates.

[0066] The treated and infiltrated veneer may then undergo a first compression step. In some examples, the treated and infiltrated veneer may be loaded into a press, wherein the temperature of the top and bottom platens of the press is in the range of about 20-150°C. The treated and infiltrated veneer may be oriented in the press so that the thickness axis of the veneer is orthogonal to the contact surface of the platens. The pressure applied to the treated and infiltrated veneer may increase from 0 to about 3-8 MPa over a period of 0-10 minutes. The applied pressure may then be maintained until the treated and infiltrated veneer has been compressed to about 40-50% of its original thickness. At this point, the density of the treated and infiltrated veneer may be about 900-1,100 kg / m 3 . The compression process may take about 5-100 minutes, depending on the original thickness of the treated and infiltrated veneer, the pressure applied, the temperature of the press plate, the wood species and other factors (including those related to the first step in the process). The pressure applied to the treated and infiltrated veneer can then be released, and the treated, infiltrated and compressed veneer can then be removed from the press. In some examples, for the first compression step, it may be beneficial for the temperature of the press plate to be in the range of about 20-60°C. Lower temperatures may help ensure that the absorbed water-blocking agent is not cured during this step. Partial degradation of lignin (and / or hemicellulose) during the first stage of the manufacturing process, which involves treating the veneer with a loading solution and then heating it, may help to perform compression at these lower temperature values.

[0067] The treated, infiltrated and compressed sections of the veneer may then be subjected to a second drying step. In some examples, the treated, infiltrated and compressed veneer may be dried to a moisture content of about 1-10%. Drying may be accomplished by using a kiln or oven. Alternatively, drying may be accomplished in a chamber operated under reduced pressure. In some examples, the treated, infiltrated and compressed veneer may be restrained in a manner that prevents dimensional deformation (warping or distortion) from occurring during the drying process. Drying under reduced pressure and at low temperatures may be preferred to ensure that the absorbed water-blocking agent is not solidified during the drying process in this step.

[0068] The treated, infiltrated, compressed and dried veneer may then be subjected to a second compression step. The treated, infiltrated, compressed and dried veneer may be loaded into a press, wherein the temperature of the top and bottom platens of the press is in the range of about 20-150° C. The veneer may be oriented in the press so that the thickness axis of the veneer is orthogonal to the contact surface of the platens. The pressure applied to the treated, infiltrated, compressed and dried veneer may be increased from 0 to about 3-10 MPa over a period of 0-10 minutes. The applied pressure may then be maintained until the treated, infiltrated, compressed and dried veneer has been compressed to a pressure corresponding to a density of about 1,100-1,400 kg / m 3 In some examples, the density of the treated, infiltrated, compressed, and dried veneer may be increased to greater than about 1,300 kg / m 3 In some examples, the density of the treated, infiltrated, compressed, and dried veneer may be increased to greater than about 1,350 kg / m 3 value. Depending on the original thickness of the veneer, the pressure applied, the temperature of the press plate, the type of wood, and other factors (including factors related to the first step in the process), the second compression process may take about 2-40 minutes. In some examples, after complete compression of the veneer has been achieved, the water-blocking agent in the treated, infiltrated and compressed veneer may be cured or otherwise converted into a polymerized state so that it is insoluble in water. The purpose of this technology is to cure the water-blocking agent after the treated, infiltrated, compressed and dried veneer has reached the final compression target. In some examples, the water-blocking agent may be cured before the pressure on the treated, infiltrated, compressed and dried veneer has been released. In some examples, the water-blocking agent may be cured after the pressure on the treated, infiltrated, compressed and dried veneer has been released. For example, the treated, infiltrated, compressed and dried veneer can be fully compressed to about 1,200-1,400kg / m 3The treated, infiltrated, compressed and dried veneer is removed from the press and transferred to a kiln or oven to cure the absorbed water-blocking agent. In some examples, the treated, infiltrated, compressed and dried veneer may be constrained in a kiln or oven to prevent the formation of geometric defects (e.g., distortion or warping).

[0069] The treated, infiltrated, and compressed veneer produced according to the present disclosure may exhibit improved dimensional stability when exposed to water. The amount of expansion along the thickness axis may be greatly reduced by using a water blocker. In some examples, the amount of expansion along the thickness axis may be less than about 5% by using a water blocker.

[0070] Thus, veneer products and veneer-based wood chip products produced according to the methods disclosed herein may achieve a non-normal distribution (ie, a truncated distribution) of properties, avoiding low value outliers by using the methods disclosed herein.

[0071] The veneer products and veneer-based wood chip products produced according to the methods disclosed herein can therefore meet or exceed target performance values. In some examples, the average along-the-grain flexural modulus of the veneer products and veneer-based wood chip products can be at least 1.8 x 10 6 psi, at least 2.0x 10 6 psi, at least 2.2x 10 6 psi or at least 2.4x 10 6 In some examples, the minimum along-the-grain flexural modulus of the veneer products and veneer-based wood chip products may be at least 1.8 x 10 6 psi, at least 2.0x10 6 psi, at least 2.2x 10 6 psi or at least 2.4x 10 6 In some examples, the average density of the veneer products and veneer-based wood chip products may be at least 800 kg / m 3 , at least 1,000kg / m 3 , at least 1,200kg / m 3 or at least 1,400kg / m 3 In some examples, the minimum density of the veneer products and veneer-based wood chip products may be at least 800 kg / m 3 , at least 1,000kg / m 3 , at least 1,200kg / m 3 or at least 1,400kg / m 3 .

[0072] According to some aspects of the present disclosure, a veneer product produced according to the methods disclosed herein can be used in a variety of products. In some examples, the product can be a composite material including one or more veneer layers produced according to the methods disclosed herein. In some examples, the product can be a plywood product including two or more veneer layers produced according to the methods disclosed herein. In some examples, the product can be an I-beam having a central web section and an outer top flange section and an outer bottom flange section. In such an example, the flange section can include a veneer layer produced according to the methods disclosed herein.

[0073] According to some aspects of the present disclosure, the improved veneer-based wood chips produced according to the methods disclosed herein can be used in a variety of products. In some examples, the product can be an oriented strand board product including veneer-based wood chips produced according to the methods disclosed herein. In some examples, the product can be a parallel-laminated wood product including veneer-based wood chips produced according to the methods disclosed herein. In some examples, the product can be a laminated wood product including veneer-based wood chips produced according to the methods disclosed herein.

[0074] Working Examples of the Disclosed Technology

[0075] In the comparative example, 8 small samples of natural yellow poplar veneers were measured for longitudinal flexural modulus. See Table 1. Likewise, four small samples of yellow poplar veneers from the same population as the control group were subjected to the disclosed veneer improvement process and then measured for longitudinal flexural modulus. See Table 2. Flexural modulus values ​​were determined using the ASTM D1037 method.

[0076] Table 1. Flexural modulus and related parameters of natural yellow poplar wood group

[0077]

[0078] Table 2. Flexural modulus and related parameters of the modified yellow poplar group

[0079]

[0080]

[0081] Assuming that the flexural modulus values ​​in the natural yellow poplar group are normally distributed, based on the data shown in Table 1, it can be calculated that 78.2% of the veneer samples in the natural yellow poplar population will have flexural modulus values ​​less than 1,800,000 psi.

[0082] In contrast, based on the data shown in Table 2, it is calculated that approximately 0.0% of the veneer samples in the modified yellow poplar population will have a flexural modulus value less than 1,800,000 psi. Therefore, if the desired flexural modulus value for a veneer in a LVL application is 1,800,000 psi, then all of the veneers in this modified group will be suitable for use in structural LVL applications.

[0083] In some examples of the present disclosure, wooden elements (e.g., sliced ​​wood, wood chips, planks, particles, fibers, or other wooden elements) may be subjected to the processes described herein. In this manner, a population of wooden elements of different types having initial flexural modulus properties (wherein a portion of the population has unacceptable flexural modulus values ​​and another portion of the population has acceptable flexural modulus values) may be subjected to a process that effectively transforms the entire population so that all wooden elements have acceptable flexural modulus values.

[0084] Additional Examples of the Disclosed Technology

[0085] In view of the above-mentioned embodiments of the disclosed subject matter, the present application discloses the additional examples listed below. It should be noted that a single feature of an example or more than one feature of the example obtained in combination and optionally obtained in combination with one or more features of one or more other examples are other examples that also fall within the scope of the disclosure of the present application.

[0086] Example 1. A method comprising: subjecting a group of wood veneer sections to non-destructive along-grain bending modulus measurement; classifying the veneer sections into a first group having modulus values ​​above a predetermined threshold and a second group having modulus values ​​below the threshold; and subjecting the second group of veneer sections to a process of increasing the along-grain bending modulus values ​​to a value greater than the predetermined threshold.

[0087] Example 2. A method as described in any example herein (especially Example 1), wherein the process of increasing the longitudinal bending modulus value comprises a lignin degradation step and a compression step.

[0088] Example 3. A method as described in any of the examples herein (particularly Example 1), wherein the process used to increase the longitudinal bending modulus value includes: infiltrating a veneer with a loading solution to produce a treated veneer; infiltrating the treated veneer with a water-blocking agent; compressing the treated veneer along the thickness axis until the density of the treated veneer is within a first density range; reducing the moisture content of the treated veneer to a range of approximately 1-10%; and compressing the treated veneer along the thickness axis until the density of the treated veneer is within a second density range.

[0089] Example 4. A method as described in any example herein (especially Example 3), wherein the loading solution is sodium hydroxide, sodium sulfite or a combination thereof.

[0090] Example 5. A method as described in any example herein (especially Example 3), wherein the loading solution is a non-volatile amine including ethanolamine, diethanolamine, triethanolamine and hydroxylamine or a combination thereof.

[0091] Example 6. A method as described in any example (especially Example 3) of this document, wherein the water-blocking agent is a hydrophilic reactive monomer (including hydroxymethylated phenol), a hydroxymethylated substituted phenol (including hydroxymethylated cresol) or a combination thereof.

[0092] Example 7. A method as described in any example (especially example 3) herein, wherein the water blocking agent is isocyanate.

[0093] Example 8. A method as described in any example herein (especially Example 3), wherein the first density range is about 900-1,200 kg / m 3 .

[0094] Example 9. A method as described in any example herein (especially Example 3), wherein the second density range is about 1,200-1,400 kg / m 3 .

[0095] Example 10. A method as described in any example herein (particularly Example 3), wherein the treated single sheet has a flexural modulus along the grain direction of the long axis of about 14-50 GPa.

[0096] Example 11. A method as described in any of the examples herein (particularly Example 1), wherein the process for increasing the longitudinal bending modulus value includes: infiltrating a veneer with a loading solution to form a treated veneer; reducing the moisture content of the treated veneer to a range of approximately 1-20%; and compressing the treated veneer along the thickness axis until the density of the treated veneer is within a target density range.

[0097] Example 12. A method as described in any example herein (especially Example 11), wherein the loading solution is sodium hydroxide, sodium sulfite or a combination thereof.

[0098] Example 13. A method as described in any example herein (especially Example 11), wherein the loading solution is a non-volatile amine including ethanolamine, diethanolamine, triethanolamine, hydroxylamine or a combination thereof.

[0099] Example 14. A method as described in any example herein (especially Example 11), wherein the target density range is about 800-1,400 kg / m 3 .

[0100] Example 15. A method as described in any example herein (particularly Example 11), wherein the treated single sheet has a flexural modulus along the grain direction along the long axis of about 14-50 GPa.

[0101] Example 16. The method as described in any example herein (especially Example 1), wherein the threshold value is greater than about 1.8 x 10 6 psi.

[0102] Example 17. A method as described in any example herein (especially Example 1), wherein the threshold is greater than about 2.0 x 10 6 psi.

[0103] Example 18. The method of any example herein (particularly Example 1), wherein the threshold is greater than about 2.2 x 10 6 psi.

[0104] Example 19. The method of any example herein (particularly Example 1), wherein the threshold is greater than about 2.4 x 10 6 psi.

[0105] Example 20. A composite material, wherein the composite material comprises a material produced by the method described in any example herein (particularly example 1).

[0106] Example 21. A composite material comprising two or more veneer layers, wherein one or more of the veneer layers originate from a conventional veneer manufacturing process; and wherein one or more of the veneer layers are the product of a process used to increase the flexural modulus value in the along-the-grain direction of the veneer layers, the process comprising a lignin degradation step and a compression step.

[0107] Example 22. An I-beam having a central web section and outer top flange sections and outer bottom flange sections, wherein the flange sections are formed of laminated veneer glulam, and one or more veneer layers located on the outermost side of the web are the product of a process for increasing the bending modulus value of the one or more veneer layers in the longitudinal direction of the grain, the process comprising a lignin degradation step and a compression step.

[0108] Example 23. A composite material comprising two or more veneer plies, wherein all of the veneer plies are the product of a process for increasing the values ​​of the flexural modulus along the grain of the veneer plies, the process comprising a lignin degradation step and a compression step.

[0109] Example 24. A system, wherein the system includes a population of veneer sheets, the population of veneer sheets having a non-normal truncated distribution of flexural modulus values ​​such that all veneer sheets in the population have a flexural modulus greater than 1.8x10 6 The flexural modulus value at a predetermined flexural modulus threshold of psi.

[0110] Example 25. A plywood product, wherein the plywood product comprises two or more veneer layers, at least one of the veneer layers being derived from a conventional veneer manufacturing process; and wherein at least one of the veneer layers is the product of a process used to increase the longitudinal flexural modulus value of the veneer layers, the process comprising a lignin degradation step and a compression step.

[0111] Example 26. A plywood product comprising a plurality of veneer plies, wherein all of the veneer plies are the product of a process for increasing the values ​​of the flexural modulus along the grain of the veneer plies, the process comprising a lignin degradation step and a compression step.

[0112] Example 27. A parallel wood ply glued wood product comprising a plurality of veneer-based wood sheets, wherein at least 1 weight percent of the veneer-based wood sheets are derived from a conventional veneer manufacturing process; and wherein at least 1 weight percent of the veneer-based wood sheets are the product of a process used to increase the longitudinal bending modulus value of the veneer-based wood sheets, the process comprising a lignin degradation step and a compression step.

[0113] Example 28. A parallel-ply glued-laminated wood product comprising a plurality of veneer-based wood sheets, wherein all of the veneer-based wood sheets are the product of a process for increasing the values ​​of the flexural modulus along the grain of the veneer-based wood sheets, the process comprising a lignin degradation step and a compression step.

[0114] Example 29. A laminated wood product comprising a plurality of wood chips, wherein at least 1% by weight of the wood chips are derived from a conventional wood chip manufacturing process; and wherein at least 1% by weight of the wood chips are the product of a process used to increase the longitudinal flexural modulus value of the wood chips, the process comprising a lignin degradation step and a compression step.

[0115] Example 30. A laminated wood product comprising a plurality of wood sheets, wherein all of the wood sheets are the product of a process for increasing the along-the-grain flexural modulus values ​​of the wood sheets, the process comprising a lignin degradation step and a compression step.

[0116] Example 31. An oriented strand board product comprising a plurality of wood chips, wherein at least 1 weight percent of the wood chips are derived from a conventional wood chip manufacturing process; and wherein at least 1 weight percent of the wood chips are the product of a process used to increase the longitudinal flexural modulus value of the wood chips, the process comprising a lignin degradation step and a compression step.

[0117] Example 32. An oriented strand board product comprising a plurality of wood chips, wherein all of the wood chips are the product of a process for increasing the along-the-grain flexural modulus values ​​of the wood chips, the process comprising a lignin degradation step and a compression step.

[0118] Example 33. A construction method in which a composite product is used; wherein the composite product includes a veneer, the veneer is the product of a process used to increase the flexural modulus value of the veneer in the direction of the grain, the process including a lignin degradation step and a compression step; and wherein the composite product allows for increased spacing between structural members in a building.

[0119] Example 34. A construction method in which a composite product is used; wherein the composite product includes a veneer, the veneer is the product of a process used to increase the flexural modulus value of the veneer in the direction of the grain, the process including a lignin degradation step and a compression step, and wherein the composite product allows for the use of reduced floor thickness in a building.

[0120] Example 35. A method for improving the mechanical properties of a wood veneer, the method comprising infiltrating the wood veneer with a loading solution to produce a treated veneer; partially drying the treated veneer for a first time; infiltrating the treated veneer with a water barrier; partially drying the treated veneer for a second time; maintaining the treated veneer at a temperature of 20-50°C and a pressure of 100-1,200 psi until the density of the treated veneer is 900-1,100 kg / m 3 The water-blocking agent is not completely cured; the treated veneer is dried until the moisture content is 1% to 10%.

[0121] In view of the many possible ways in which the principles of the present disclosure can be applied, it should be recognized that the illustrated configurations depict examples of the disclosed technology and should not be considered to limit the scope of the present disclosure or the scope of the claims. Instead, the scope of the claimed subject matter is defined by the appended claims and their equivalents.

Claims

1. A method comprising: subjecting a set of wood veneer sections to non-destructive along-grain flexural modulus measurements; classifying the veneer sections into a first group and a second group, the first group comprising the veneer sections having modulus values ​​above a predetermined threshold, the second group comprising the veneer sections having modulus values ​​below the threshold; as well as The second group of veneer sections is subjected to a process of increasing the with-grain flexural modulus value to a value greater than the predetermined threshold.

2. The method of claim 1, wherein: The process of increasing the along-grain bending modulus value includes a lignin degradation step and a compression step.

3. The method of claim 1, wherein: The process for increasing the along-the-grain bending modulus value comprises: infiltrating the veneer with a loading solution to produce a treated veneer; Penetrating the treated veneer with a water-blocking agent; compressing the treated veneer along a thickness axis until a density of the treated veneer is within a first density range; reducing the moisture content of the treated veneer to a range of about 1-10%; and The treated veneer is compressed along the thickness axis until a density of the treated veneer is within a second density range.

4. The method of claim 3, wherein: The loading solution is sodium hydroxide, sodium sulfite or a combination thereof.

5. The method of claim 3, wherein: The loading solution is a non-volatile amine including ethanolamine, diethanolamine, triethanolamine and hydroxylamine or a combination thereof.

6. The method of claim 3, wherein: The water blocking agent is a hydrophilic reactive monomer including hydroxymethylated phenol, a hydroxymethylated substituted phenol including hydroxymethylated cresol, or a combination thereof.

7. The method of claim 3, wherein: The water blocking agent is isocyanate.

8. The method of claim 3, wherein: The first density range is about 900-1,200 kg / m 3 .

9. The method of claim 3, wherein: The second density range is about 200-1,400 kg / m 3 .

10. The method of claim 3, wherein: The treated veneer has a flexural modulus along the longitudinal direction of the grain of about 14-50 GPa.

11. The method of claim 1, wherein: The process for increasing the along-the-grain bending modulus value comprises: infiltrating the veneer with a loading solution to form a treated veneer; reducing the moisture content of the treated veneer to a range of about 1-20%; and The treated veneer is compressed along a thickness axis until the density of the treated veneer is within a target density range.

12. The method of claim 11, wherein: The loading solution is sodium hydroxide, sodium sulfite or a combination thereof.

13. The method of claim 11, wherein: The loading solution is a non-volatile amine including ethanolamine, diethanolamine, triethanolamine, hydroxylamine, or a combination thereof.

14. The method of claim 11, wherein: The target density range is about 800-1,400 kg / m 3 .

15. The method of claim 11, wherein: The treated veneer has a flexural modulus along the longitudinal direction of the grain of about 14-50 GPa.

16. The method of claim 1, wherein: The threshold is greater than about 1.8 x 10 6 psi.

17. The method of claim 1, wherein: The threshold is greater than about 2.0 x 10 6 psi.

18. The method of claim 1, wherein: The threshold is greater than about 2.2 x 10 6 psi.

19. The method of claim 1, wherein: The threshold is greater than about 2.4 x 10 6 psi.

20. A method for improving the mechanical properties of a wood veneer, comprising: infiltrating the wood veneer with a loading solution to produce a treated veneer; subjecting the treated veneer to a first partial drying; Penetrating the treated veneer with a water-blocking agent; performing a secondary partial drying on the treated veneer; The treated veneer is maintained at a temperature of 20-50°C and a pressure of 100-1,200 psi until the density of the treated veneer is between 900-1,100 kg / m 3 , but not until the water-blocking agent is completely cured; and The treated veneer is dried until the moisture content is 1% to 10%.

21. An article comprising two or more veneer layers, wherein: One or more of the veneer layers originate from a conventional veneer manufacturing process; and wherein one or more of the veneer layers are the product of a method as claimed in any one of claims 1-20.

22. An I-beam having a central web section and outer top and bottom flange sections, wherein: The flange section is made of laminated veneer timber, and one or more veneer layers located at the outermost side of the web section are the product of the method according to any one of claims 1-21.

23. An article comprising two or more veneer layers, wherein: All of the veneer layers are the product of a method as claimed in any one of claims 1-21.

24. A system, wherein: The system includes a population of veneer sheets having a non-normal truncated distribution of flexural modulus values ​​such that all veneer sheets in the population have a flexural modulus greater than 1.8 x 10 6 The flexural modulus value at a predetermined flexural modulus threshold of psi.

25. An article of manufacture comprising a plurality of veneer-based wood sheets, wherein: At least 1% by weight of said veneer wood chips originate from a conventional veneer manufacturing process; and wherein at least 1% by weight of said veneer wood chips are the product of the method of any one of claims 1-21.

26. An article of manufacture comprising a plurality of veneer-based wood sheets, wherein: All of the veneer wood chips are the product of the method according to any one of claims 1-21.